UPAYA BADAN PENANGGULANGAN BENCANA DAERAH DALAM PENANGGULANGAN DAN PENCEGAHAN KEBAKARAN HUTAN DAN LAHAN DI KOTA PONTIANAK - M Awal Uddin; Ul Qadri; Didi Zulianto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Prof Dr Hazairin, SH, 2021)
This study aims to determine the efforts of BPBD Pontianak City and to find out the obstacles of BPBD in overcoming and preventing forest and land fires in Pontianak City, West Kalimantan Province. The research method used is a qualitative descriptive study with a study approach. informants, observations and documentation. The data analysis technique used is interactive model analysis (Miles and Huberman), namely reducing data, presenting data, drawing conclusions and verifying. While the validity of the data obtained from data triangulation, member check and adequacy of references. The results of the study show that forest and land fires in Pontianak City are caused by extreme hot weather and there are also factors of human negligence and intentional failure to comply with government regulations. Pontianak City BPBD mobilizes its resources to deal with land fires such as providing counseling and immediately going down to extinguish the fire at the point where the fire occurs. The government's implementation of land fire prevention can be carried out optimally.